The Impact of Tax Knowledge, the Adoption of Electronic Tax Filing, and Tax Penalties on Individual Taxpayers’ Compliance in Filing Annual Tax Returns - Hollines Luahambowo; Muhammad Rizal; Ngadi Permana (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study examines how tax knowledge, the use of e-filing systems, and the enforcement of tax penalties influence individual taxpayers’ compliance in filing annual tax returns. Tax compliance is a critical factor for the sustainability of government revenue, yet public compliance rates remain suboptimal. The research employs a quantitative approach with an associative causal design, involving 131 respondents in West Jakarta selected through convenience sampling. The instrument, consisting of a questionnaire with 34 items, was tested for validity and reliability and then analyzed using multiple linear regression with the aid of SPSS. The results of the analysis indicate that tax knowledge, the use of e-filing, and tax penalties have a positive effect—both partially and simultaneously—on compliance with annual tax return filing. These findings underscore the need to improve tax literacy, strengthen the e-filing system, and ensure consistent enforcement of penalties to encourage compliance. This study provides an empirical basis for the development of more inclusive and efficient tax policies and supports the government’s strategy to optimize state revenue by raising taxpayer awareness and fostering a sense of responsibility.